The formation of volunteer movements in Russia: development problems and dynamics - A. M. Kushkhova; A. A. Kubova (Вестник Майкопского государственного технологического университета)
The research is determined by the fact that the role of social movements in the modern world is increasing due to the deterioration of the socio-economic and political situations. Today, the global economic crisis has a negative impact on the condition of the most vulnerable segments of the population. The global community sees the potential in volunteer organizations to provide assistance where it is urgently needed: from healthcare to emergency response. The problem of the research is that volunteering turned out to be a new phenomenon that requires legal and public support for Russia in the post-Soviet period. In the research the methods of sociocultural analysis were used based on scientific literature and regulatory sources, statistical data on the work of volunteer organizations in Russia, both at federal and regional levels. The key conclusion is the need for public recognition and financial incentives for non-profit public organizations involved in volunteering. The state must regulate the legal framework for the activities of NPOs, develop and adopt a unified set of legal norms for application at the federal and regional levels of government. At the same time, it cannot be denied that volunteer movements are already playing one of the cool roles in the formation of patriotism, socially oriented consciousness and the education of the younger generation.